2011
DOI: 10.1021/es2012512
|View full text |Cite
|
Sign up to set email alerts
|

Distribution, Characteristics, and Worldwide Inventory of Dioxins in Kaolin Ball Clays

Abstract: Distribution, characteristics, and global inventory of dioxins (polychlorinated dibenzo-p-dioxins [PCDDs] and dibenzofurans [PCDFs] and dioxin like polychlorinated biphenyls) in kaolin clays collected from 10 countries were investigated. Dioxins were found in all kaolin clay samples analyzed, at total concentrations ranging from 1.2 pg/g (Brazil) to 520,000 pg/g (USA). Dioxin concentrations in kaolin clays from a few countries (e.g., Brazil and UK) were lower than those reported for background soils in Japan. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 25 publications
2
24
0
Order By: Relevance
“…PCDFs were not detected or were found at the ultra trace level in the samples. These results were very similar to previous studies that reported PCDD/Fs in kaolinitic clays were characterized by congener profiles dominated by OCDD and HpCDDs and trace levels of PCDFs [1,2,5,13].…”
Section: Congener Profiles Of Pcdd/fs In the Test Piecessupporting
confidence: 92%
See 3 more Smart Citations
“…PCDFs were not detected or were found at the ultra trace level in the samples. These results were very similar to previous studies that reported PCDD/Fs in kaolinitic clays were characterized by congener profiles dominated by OCDD and HpCDDs and trace levels of PCDFs [1,2,5,13].…”
Section: Congener Profiles Of Pcdd/fs In the Test Piecessupporting
confidence: 92%
“…The samples were extracted using toluene for 24 h in a Soxhlet apparatus, and the extracts were concentrated on a rotary evaporator. The extracts were then sequentially purified using acidic silica-gel columns (44 wt.% sulfuric acid-impregnated silica gel) and 10 wt.% silver nitrate-impregnated silica gel [2,7]. The analyte was fractionated using an active carbon column (50 wt.% active carbon-blended silica gel and 50 wt.% active carbon dispersed silica gel).…”
Section: Sample Preparationmentioning
confidence: 99%
See 2 more Smart Citations
“…A 1976 study of PCB adsorption on soils showed that illite (a clay mineral) was highly adsorptive for the three congeners tested, with higher adsorption for highly chlorinated congeners (Haque and Schmedding, 1976). PCBs and PCDD/Fs have been detected in types of clay that are often eaten (Horii et al, 2011; Reeuwijk et al, 2013), but we had no information on PCB concentrations in local clay.…”
Section: Discussionmentioning
confidence: 99%